2013
DOI: 10.1371/journal.pone.0074738
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SIRT1 and DBC1 Is Associated with Poor Prognosis of Soft Tissue Sarcomas

Abstract: Recently, the roles of SIRT1 and deleted in breast cancer 1 (DBC1) in human cancer have been extensively studied and it has been demonstrated that they are involved in many human carcinomas. However, their clinical significance for soft-tissue sarcomas has not been examined. In this study, we evaluated the expression and prognostic significance of the expression of SIRT1, DBC1, P53, β-catenin, cyclin D1, and KI67 in 104 cases of soft-tissue sarcomas. RESULTS: Immunohistochemical expression of SIRT1, DBC1, P53,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 52 publications
4
65
1
Order By: Relevance
“…Indeed, regulation of p53 by CCAR2 appears to be important for tumor initiation in some tissues, as Ccar2 −/− mice have increased tumor incidence compared to wild-type controls, dependent on p53 but Sirt -independent (Qin et al , 2015). In contrast to this data, many tumor types have been reported to have high expression of CCAR2, and this correlates with poor clinical outcomes (Cha et al , 2009; Cho et al , 2015; Kim et al , 2013; Kim et al , 2012; Yu et al , 2015; Yu et al , 2013; Zhang et al , 2014). In addition, the large majority of SCC tumors have mutated or lost p53 (Giglia-Mari and Sarasin, 2003), while CCAR2 is rarely altered in human cancer (Cerami et al , 2012), suggesting there may be p53-independent roles for CCAR2 in SCC.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Indeed, regulation of p53 by CCAR2 appears to be important for tumor initiation in some tissues, as Ccar2 −/− mice have increased tumor incidence compared to wild-type controls, dependent on p53 but Sirt -independent (Qin et al , 2015). In contrast to this data, many tumor types have been reported to have high expression of CCAR2, and this correlates with poor clinical outcomes (Cha et al , 2009; Cho et al , 2015; Kim et al , 2013; Kim et al , 2012; Yu et al , 2015; Yu et al , 2013; Zhang et al , 2014). In addition, the large majority of SCC tumors have mutated or lost p53 (Giglia-Mari and Sarasin, 2003), while CCAR2 is rarely altered in human cancer (Cerami et al , 2012), suggesting there may be p53-independent roles for CCAR2 in SCC.…”
Section: Discussioncontrasting
confidence: 74%
“…Clinical studies across a variety of tumor types, including SCC, have suggested that high levels of CCAR2 ( C ell C ycle activator and A poptosis R egulator 2; also known as DBC1) may be an indicator of poor outcomes (Chen et al , 2014; Kim et al , 2013; Kim et al , 2012; Yu et al , 2013), and could potentially have pro-tumorigenic functions. However, studies in Ccar2 − / − mice suggest that Ccar2 may function as a tumor-suppressor, although SCC did not develop in these mice (Qin et al , 2015).…”
Section: Intoductionmentioning
confidence: 99%
“…SIRT1 is also overexpressed in non-melanoma skin cancers, including squamous and basal cell carcinomas, actinic keratosis, and especially in Bowen's disease [16]. Further, the overexpression of SIRT1 has been linked to poor disease prognosis and survival in variety of cancers [17-19]. However, the role of SIRT1 is quite puzzling as there is an ongoing debate regarding its role as a tumor suppressor versus tumor promoter [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that SIRT1-defective or knockdown cells have an increased apoptotic response to DNA damage or oxidative stress treatments (12 indicated a role for SIRT1 in tumorigenesis, its role in cancer has not been sufficiently studied. For example, SIRT1 demonstrates anti-oncogene action in colon cancer and its expression level is associated with prognosis, but it is considered to exhibit oncogenic action in breast cancer (13,14). A previous study indicated that tumors in SIRT1-deficient mice have markedly increased numbers of cells undergoing apoptosis (15).…”
Section: Introductionmentioning
confidence: 99%